Health Counseling to Increase Ma’arif MA Students’ Knowledge of Covid 19 Vaccination - Lubis, Novriyanti; Rosilia, Novita; Sution, Sution; Widia, Putri; Nugraha, Robi Asran; Aladawi, Syifa; Taufikurrohman, Ikbal (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Starting the new academic year 2021 of Indonesian education, since the COVID-19 pandemic, the government plans to implement new policies, one of which is the implementation of vaccines for students, where the aim is to accelerate the prevention of COVID-19 in Indonesia and can also be used as a requirement for schools to hold face-to-face learning advance. To support this government program, everyone 12 years of age and older in now eligible to get a Covid 19 vaccination the University Pharmacy team through the Community Service Program in Cikelet village wants to contribute knowledge and knowledge to Madrasah Aliyah Ma’arif school students through health education on the topic of the importance of vaccination for students. The activity begins with a pretest and then provides counseling related to the topic vaccination and continues with a posttest where the expected output is an increase in students’ knowledge of the material.